Pengobatan Gratis Bagi Masyarakat Desa Swarangan Kecamatan Jorong - Dwi Wulan Apriani; Ahmad Nurwanto; Melly Anisa Putri; Yanti Fauziah; Adelina Sisilia; Ika Pratiwi; Tio Widia Astuti Marpaung; M. Husein Syawaludin; Dinda Nafilla; Dyah Ayu Fatmawati (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
Limited public awareness of routine health check-ups and healthy lifestyle practices contributes to various untreated health problems in the community. This community service program aimed to increase public awareness and promote early detection of health conditions through free medical screening services. The activity was conducted by lecturers and students of Borneo Citra Medika Polytechnic of Health in collaboration with Borneo Citra Medika Hospital. A total of 52 participants, predominantly housewives, attended the program. The methods included medical anamnesis, basic physical examinations, and health consultations. The results showed that 15 participants experienced myalgia, 7 reported toothache, 6 had gastritis, and 6 had cough, while others presented with asthma, diabetes mellitus, hypertension, fever, and allergies. The program improved community awareness regarding the importance of regular health check-ups and early detection. Sustainable community-based screening activities are recommended to strengthen preventive and promotive health efforts and improve overall community health outcomes.